2012
DOI: 10.2217/fon.12.76
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Actions of PTHrP in Skeletal Metastasis

Abstract: PTHrP, identified during the elucidation of mediators of malignancy-induced hypercalcemia, plays numerous roles in normal physiology as well as pathological conditions. Recent data support direct functions of PTHrP in metastasis, particularly from tumors with strong bone tropism. Bone provides a unique metastatic environment because of mineralization and the diverse cell populations in the bone marrow. PTHrP is a key regulator of tumor–bone interactions and regulates cells in the bone microenvironment through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 99 publications
0
86
0
1
Order By: Relevance
“…PTHrP expression is commonly found in many types of cancers, including the breast, and it can promote tumor growth and metastasis (67,68). While PTH and PTHrP have similar binding affinities to the G protein-coupled PTH1R, PTH binds with greater stability than the PTHrP, facilitating prolonged signaling even after internalization of the ligand-receptor complex, resulting in different downstream effects (69).…”
Section: Discussionmentioning
confidence: 99%
“…PTHrP expression is commonly found in many types of cancers, including the breast, and it can promote tumor growth and metastasis (67,68). While PTH and PTHrP have similar binding affinities to the G protein-coupled PTH1R, PTH binds with greater stability than the PTHrP, facilitating prolonged signaling even after internalization of the ligand-receptor complex, resulting in different downstream effects (69).…”
Section: Discussionmentioning
confidence: 99%
“…RANKL binds the RANK receptor on osteoclast precursors and promotes osteoclastogenesis. In turn, bone resorption by osteoclasts releases other peptides which can promote tumor growth (i.e., TGF-β, IGFs and PDGF) [22]. PTH can also stimulate the osteoblast niche within the bone marrow.…”
Section: Why Is the Effect Of Adjuvant Clodronate Not Inferior When Cmentioning
confidence: 99%
“…PTH is similar to PTH-related peptide (PTHrp) and both PTHrp and PTH share the same receptor (PTHR1) which is expressed on different types of cancers. The interaction of PTH/PTHrp with PTHR1 can promote cell proliferation and growth, resistance to apoptosis, invasion and metastasis [22]. Of note, a post hoc analysis of a randomized placebo-controlled trial evaluating zoledronic acid for metastatic prostate cancer reported that elevated serum PTH levels could predict worse outcomes in patients treated with zoledronic acid [25].…”
Section: Why Is the Effect Of Adjuvant Clodronate Not Inferior When Cmentioning
confidence: 99%
“…The PTHrP protein is a polyhormone with multiple biologically active domains conferring different actions as an autocrine, paracrine, endocrine, and intracrine hormone [Soki et al, 2012]. It has many biological actions during fetal growth and development and throughout life [Strewler, 2000].…”
Section: Introductionmentioning
confidence: 99%